Anti-ICOS agonist antibodies and uses thereof - Engelhardt, John J; Stevens, Brenda L; Selby, Mark J; Korman, Alan J; Feingersh, Mary Diane (2019)
The present invention provides isolated monoclonal antibodies (e.g., humanized and human monoclonal antibodies) that bind to human Inducible T Cell COStimulator (ICOS) and exhibit therapeutically desirable functional properties, e.g., the ability to stimulate human ICOS activity. Nucleic acid molecules encoding the antibodies of the invention, expression vectors, host cells, and methods for expressing the antibodies of the invention are also provided. Immunoconjugates, bispecific molecules, and pharmaceutical compositions comprising the antibodies of the invention are also provided. The antibodies of the invention can be used, for example, as an agonist to stimulate or enhance an immune response in a subject, e.g., antigen-specific T cell responses against a tumor or viral antigen. The antibodies of the invention can also be used in combination with other antibodies (e.g., PD-1, PD-L1, and/or CTLA-4 antibodies) to treat, for example, cancer. Accordingly, the antibodies can be used in therapeutic applications and methods to detect ICOS protein.